Longitudinal Follow-Up of the Psychological Well-Being of Patients with Colorectal Cancer: Final Analysis of PICO-SM - Konstantinos Kamposioras; Panagiotis Ntellas; Katerina Dadouli; Eleftherios Christodoulis; Marios Adamou; Daniel Anderson; Anup Shanthappa; Jacqueline Connell; Joseph Williams; Lilly Simpson; Theodora Germetaki; Michael Braun; et al. (Current Oncology)
PICO-SM was a prospective longitudinal study investigating the psychological impact of the COVID-19 pandemic on patients with colorectal cancer treated in a large UK tertiary cancer centre. Here, we present the impact of the third wave of the pandemic (December 2021 to February 2022), when the Omicron variant became prevalent in the UK, and the complete longitudinal comparison across the entire duration of this study. Patients were invited to complete a questionnaire, including screening psychometric tools. In total, n = 312 patients were included in the final analysis. Specifically, in this Omicron-predominant wave, n = 96 patients were studied in detail: the mean age was 64 years, 64% were male, 33% reported poor well-being, 27% anxiety, 11% depressive symptoms, and 3% trauma-related symptoms. The participants who had investigations cancelled (OR 9.22, 95% CI 1.09–77.85; p = 0.041) or felt that the pandemic would affect their mental health (OR 3.82, 95% CI 1.96–7.44; p < 0.001) had an increased risk of anxiety according to a multivariate analysis. Similarly, independent predictors of poor well-being included concern that the pandemic would affect their cancer treatment (OR 4.59, 95% CI 1.03–20.56; p = 0.046) or mental health (OR 3.90, 95% CI 1.38–11.03; p = 0.010). The psychological distress experienced by patients, particularly anxiety, remained high during the third wave of the COVID-19 pandemic. These results align with our previously reported findings, emphasising the importance of continuing cancer treatment amidst an ongoing humanitarian emergency.